Deroplax silphoides (Thunberg, 1783) (Hemiptera: Heteroptera: Scutelleridae) Invasive Species in Egypt with additional morphological and behavioral data - Gadallah, Sohair M.; Nasser, Mohamad G.; Farag, Shaimaa M.; Elhawary, Mohammad O.; Hossny, Alaa (Zootaxa, 2019)
Invasive species continue to be a noteworthy risk to a wide range of biological systems and species diversity throughout the world. At present, accessible data about invasive species in Egypt are still insufficient despite the genuine danger these species pose to the Egyptian environment, economy and human well-being. The present study adds new distribution records of the invasive scutellerid species, Deroplax silphoides (Thunberg, 1783), to the Egyptian fauna. In 2008, this bug was first observed in Egypt in South Sinai, followed by Giza in 2016. Recently, hundreds of specimens were reported from Cairo in 2018. A new host plant, Chrysanthemum morifolium L. (Asteraceae), is reported for this bug. This work also provides additional information about the male and female genitalia. New characteristic features, photos, examined material, map of its world distribution, ecological and behavioral notes are also provided. Moreover, egg sculpturing of Deroplax silphoides was examined for the first time.